Rizika marketingových aktivit na internetu - Bezděková, Veronika (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2014)
Diplomová práce se zabývá problematikou rizik pojicích se s marketingovými aktivitami vybrané společnosti. Teoretická část definuje pojmy související s marketingem a riziky. Praktická část se zabývá samotnou analýzou rizik marketingových aktivit a následně doporučení, které vedou k zmírnění či odstranění rizik.

This thesis deals with the risks attaching to the marketing activities of the selected company. The theoretical part defines terms associated with marketing and risks. The practical part is dedicated to the analysis of the risks of marketing activities and subsequent recommendations that lead to the reduction or elimination of risks
Risks of Marketing Activities on the Internet
Keywords: Marketing; rizika; reklama na internetu; Marketing; Risk; internet advertising